Bridged [large type] - Elliot, Kendra (Elliot, Kendra. Callahan & McLane., 2018)
"After a congressman's tortured body is found dangling from a Portland bridge, the FBI joins the Oregon State Police to investigate the case and FBI Special Agent Ava McLane, still recovering from a bullet wound, hunts the twisted killer alongside the man who captured her heart, police detective Mason Callahan in this romantic suspense novel "--